L’histoire des ordures : de la préhistoire à la fin du dix-neuvième siècle - Marine Béguin (VertigO)
The question of the waste became, as time goes by, more and more problematic because of their considerable increase. However, the awareness of the necessity of an effective management of garbage appeared only lately in human history. The objective of this article is to present, through an essentially bibliographical approach, the way the people lived and managed their waste since the Prehistory until at the end of the XIXth century.